Cytological evaluation of lymphoepithelial lesions of the major salivary glands with special reference to lymphoepithelial sialadenitis: A clinicopathological study - Rajashree Pradhan; Sajeeb Mondal; Chirasri Goswami; Suman Chatterjee (Asian Journal of Medical Sciences)
Background: Fine needle aspiration cytology (FNAC) is an accurate, reliable, minimally invasive, and cost-effective procedure for pre-operative evaluation of salivary gland lesions. Salivary glands are host to a wide range of pathological conditions ranging from reactive, inflammatory, and cystic conditions to neoplastic lesions. In comparison to the epithelial lesions, salivary gland lymphoepithelial lesions (LELs) are rare. Cytological evaluation of the salivary gland LELs was described as case reports in few literatures.